Improving the Ability to Count Money Through Role Playing Methods for Students with Disabilities - Angkat, Juliani; Budi, Setia (Juwara: Jurnal Wawasan dan Aksara, 2025)
This research aims to improve the ability of students with mild intellectual disabilities in calculating the value of money through the application of the Role Play method. The method used in this study is Classroom Action Research (PTK), which is carried out in two cycles, each consisting of two meetings and one post-test. Data were collected through observation, interviews, and documentation, and analyzed in a quantitative descriptive manner. The results of the study showed a significant increase in students' ability to calculate the value of money. The average score of students increased from 49.8 in the pre-test to 71.43 in the first cycle, and reached 89.29 in the second cycle, with a 100% pass rate. The application of Role Play provides a concrete experience that helps students connect the concept of the value of money with everyday transactions, increase motivation, and actively engage in learning. The implications of this study show that the Role Play method is effective in improving mathematical skills in students with mild intellectual disabilities. In conclusion, Role Play has been proven to significantly improve students' ability to calculate the value of money.